Parameter identification of the interaction body model using available measurements - Zhang, Qingwen (Array, 2020)
This paper determines the parameters of the interaction models based on available published experimental measurements. The masses, damping ratios and stiffnesses of body models are identified by the curve fitting of the measured apparent mass curves from shaking table tests in published biomechanics studies. Then the extracted data are used to identify the parameters of the interaction models. Finally, the eigenvalue analyses of the human-structure models are calculated for comparison. In this identification process, it was identified that the quality of the curve fitting for the interaction model is as good as and even slightly better than the published results. One or two additional conditions for the interaction models would lead to several sets of parameters, but with the result of the continuous model, reasonable parameters have to be applied which can be identified and these parameters could be used in further calculations.